The earth's blanket : traditional teachings for sustainable living - Turner, Nancy J., 1947- (Culture, place, and nature., 2005)
"Turner has worked with Native peoples in the Pacific Northwest for more than thirty-five years, and generations of her indigenous teachers have given her permission to share their stories and perspectives about the natural world. Their teachings describe a rich variety of methods of harvesting, transporting, processing, storing, maintaining, and enhancing natural resources such as trees, medicinal plants, berries, root vegetables, fish, meat, and shellfish. More than just stories, these narratives underlie a belief system that informs everyday attitudes toward the earth." "The Earth's Blanket suggests how systems of traditional ecological knowledge can contribute to the modern world."--Jacket.